The relationship between employees' perceptions of organisational climate and customer retention rates in a major UK retail bank - Clark, Moira (Cranfield University, 2000)
There has been increasing interest in the field of customer retention in the last two decades. Much of that interest has focused on the economics of customer retention and developing plans and strategies for companies to follow to improve customer retention. There has been little research into what determines customer retention, particularly from the perspective of organisational climate. The purpose of this study, therefore, is to examine the relationship between employees' perceptions of organisational climate and customer retention in a specific service setting. The methodology adopted for this study is a 'within method' triangulation approach, which uses predominantly qualitative research techniques, supported by quantitative research methods. The foundation of the research design is a set of six case studies of bank branches selected from the network of a major UK retail bank. The branches are similar to each other in every respect, except that three have high customer retention rates and three have low retention rates. The main source of data is semi-structured interviews with a representative sample of six employees from each bank branch. This data is supported by survey data from a questionnaire that was completed by an the staff in all six branches. This questionnaire was also used as a platform from which to conduct the semi-structured interviews. Cross-case analysis between the two sets of branches is undertaken using the 'stacking comparable cases' approach, in order to systematically compare and contrast the differences between the high and low retairuing branches. The findings from the study show that there is a relationship between employees' perceptions of organisational climate and customer retention at a micro-organisational level. It shows that organisational climate can be sub-divided into five climate themes and that within each climate theme there are dimensions which are critical to customer retention and others which are less critical or irrelevant. Finally, the study highlights that it is the climate themes and dimensions taken together that form the climate for 6customer care' and not the individual themes and dimensions.